Physician Variability in Treating Pain and Irritability of Unknown Origin in Children with Severe Neurological Impairment. (2013) - Siden, Harold B; Carleton, Bruce C; Oberlander, Tim F
Abstract : BACKGROUND: Pain and irritability of unknown origin (PIUO) is a challenging problem for nonverbal children with severe neurological impairments. PIUO is not associated with an identifiable source of nociceptive-inflammatory or neuropathic pain. OBJECTIVE: To assess how physicians use pharmacotherapy to treat PIUO, and to report a pilot study of a standardized approach to investigating and treating PIUO. METHOD: Part 1 of the present study involved independently presenting a case vignette of a patient with PIUO to six experienced physicians who care for children with neurological impairments. They were asked for medication choices and sequences to empirically treat PIUO. Part 2 was a pilot study of a PIUO protocol. Patients followed a standard pathway for PIUO, referred to as the pathway for unknown pain (PUP). The initial drug sequence for the PUP was based on Part 1. RESULTS: In Part 1, physicians responding to the case vignette listed eight medications (atypical antipsychotics, benzodiazepines, gabapentin, methadone, opioids, selective serotonin reuptake inhibitors, tramadol and tricylic antidepressants) and eight empiric drug sequences. In Part 2, eight children with PIUO (six to 17 years of age; five females, three males) were enrolled in a pilot clinic. Only two had been fully evaluated for nociceptive-inflammatory pain sources before enrollment. At the end of the pilot study, four patients were clinically improved and only three required a study medication. DISCUSSION AND CONCLUSION: Even experienced physicians do not agree on a common approach for medical treatment of PIUO. A standardized pathway is feasible and readily implemented. The proposed PUP has the potential to address PIUO and be the basis for future intervention studies.